Models in Returning the Harmonic Life Postconflicts as Ethnic in Sambas Regency - Setyo Utomo; Joko Martono; Aleksander Sebayang (Proceedings of AICS - Social Sciences, 2018)
The Constitution of the Republic of Indonesia 1945 has guaranteed the freedom to reside within the territory of the Unitary State of the Republic of Indonesia. Based on the experience of conflicts in the country, with the post-conflict handling of those who had previously conflicted it can be reunited in living a harmonious life, but unlike the conflict that occurred in Sambas Regency in 1999 between ethnic Malays and Madurese which has been for so many years and with post-conflict efforts that have been done until now people in Sambas district have not been able to accept the presence of Madurese in Sambas Regency. So through this article the authors want to put forward the formulation of the problem how the models can be taken so that victims of post-conflict ethnicity can return to live in place that they had previously occupied, so the goal to realize a harmonious life between two ethnic who had been involved in the conflict through the models offered by the author can be done by related authority parties.Keywords:human rights, conflict, ethnicity, harmony.